2006
DOI: 10.1177/0192513x06287168
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Assessing the Impact of Time-Varying Family Risk Factors on High School Dropout

Abstract: Human behavior is dynamic, influenced by changing situations over time. Yet the impact of the dynamic nature of important explanatory variables on outcomes has only recently begun to be estimated in developmental models. Using a risk factor perspective, this article demonstrates the potential benefits of regressing time-varying outcome measures on time-varying explanatory measures in longitudinal models. The authors apply event history analysis techniques to demonstrate a methodological strategy that accounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
3
27
1
Order By: Relevance
“…Some unknown portion of these findings may be driven by selection bias. Specifically, because childhood poverty is linked to placement in lower curricular tracks, higher risk of dropping out, and poverty later in life (Oakes, 1985;Randolph et al, 2006), some portion of the observed relationships between tracking and welfare receipt may be the result of inadequate controls for poverty early in life. I conducted supplemental analyses to examine the sensitivity of the results which demonstrated that the results are robust, even among subsamples of youth from single-parent or low-income families and whose parents had limited educational attainment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some unknown portion of these findings may be driven by selection bias. Specifically, because childhood poverty is linked to placement in lower curricular tracks, higher risk of dropping out, and poverty later in life (Oakes, 1985;Randolph et al, 2006), some portion of the observed relationships between tracking and welfare receipt may be the result of inadequate controls for poverty early in life. I conducted supplemental analyses to examine the sensitivity of the results which demonstrated that the results are robust, even among subsamples of youth from single-parent or low-income families and whose parents had limited educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have especially highlighted the role of dropping out of school for shaping individual progress toward poverty and have examined the individual, community, and family factors associated with this outcome (Haveman & Wolfe, 1994;Randolph, Fraser, & Orthner, 2006;Randolph, Rose, Fraser, & Orthner, 2004). However, we know little about the ways that more specific experiences in high school, such as the courses students take, shape welfare dynamics directly and indirectly through their effects on dropout, teen motherhood, and other negative outcomes that are closely associated with welfare receipt.…”
Section: R Beattiementioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing definitions of study engagement, Zhang Na [4] thinks study engagement means -students learn actively, think deeply and energetically meet challenges and setbacks as well as have active emotional experience‖. The existing researches have analyzed the influence factors of study engagement from the perspectives of personal factor including sex factor [5][6] and environmental factor [7][8][9]. Besides, some scholars research the influence of peer factor on study engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has posited that dropping out of school is the culmination of cumulative risk factors over time, including difficulty reading or learning math, grade retention, school disengagement, and a variety of childhood behavior problems (Randolph, Fraser, & Orthner, 2006;Randolph, Rose, Fraser, & Orthner, 2004;Simner & Barnes, 1991;Woolley & Bowen, 2007). One comprehensive study followed a cohort of children from low-income families from birth to age 19 years (Jimerson, Egeland, Sroufe, & Carlson, 2000), and found that global indices of externalizing and internalizing (measured by the Child Behavior Checklist [CBCL]) during the first grade were predictive, to some extent, of high-school dropout (see also Alexander, Entwisle, & Horsey, 1997;Bridgeland et al, 2006;French & Conrad, 2001;Garnier et al, 1997).…”
mentioning
confidence: 99%